2010
DOI: 10.2337/dc10-0524
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality Among Middle-Aged and Older Adults With Diagnosed and Undiagnosed Diabetes

Abstract: OBJECTIVETo describe sexual activity, behavior, and problems among middle-age and older adults by diabetes status.RESEARCH DESIGN AND METHODSThis was a substudy of 1,993 community-residing adults, aged 57–85 years, from a cross-sectional, nationally representative sample (N = 3,005). In-home interviews, observed medications, and A1C were used to stratify by diagnosed diabetes, undiagnosed diabetes, or no diabetes. Logistic regression was used to model associations between diabetes conditions and sexual charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 23 publications
4
51
1
2
Order By: Relevance
“…According to Jackson's research [27], persistent erectile dysfunction was observed in 34% of patients and in 24% they appeared from time to time. In the study of Lindau [28] a similar result was obtainederection problems were reported in 36% of patients. In addition, 29% of those who achieved an erection in an undisturbed way were unable to experience orgasm.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…According to Jackson's research [27], persistent erectile dysfunction was observed in 34% of patients and in 24% they appeared from time to time. In the study of Lindau [28] a similar result was obtainederection problems were reported in 36% of patients. In addition, 29% of those who achieved an erection in an undisturbed way were unable to experience orgasm.…”
Section: Discussionsupporting
confidence: 70%
“…More than half of the patients included in the study had been diagnosed with type 2 diabetes. This can have a significant impact on the emergence of a broad spectrum of disorders of sex life [25,26,28]. The combination of mature age of a patient with the diagnosis of diabetes, strongly multiplies the risk of emergence of various types of sexual problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Lindau ST et al study found high prevalence of orgasm problems in men with DM. 17 Burke JP et al and Lindau ST et al, studies suggest that diabetes increases the risk of having HSDD. 3,17 The age (p = 0.335) and duration of DM (p =0.056) are statistically not significant between the two groups in this study.…”
mentioning
confidence: 99%
“…17 Burke JP et al and Lindau ST et al, studies suggest that diabetes increases the risk of having HSDD. 3,17 The age (p = 0.335) and duration of DM (p =0.056) are statistically not significant between the two groups in this study. Veves et al study also suggest that age is not a significant factor associated with SD.…”
mentioning
confidence: 99%